Assessment of Awareness of Breast Cancer among Adult Women Attending OPD in a Tertiary Care Hospital in Krishnagiri ,Tamil Nadu - A Cross-Sectional Study (Indian Journal of Public Health Research & Development, 2025)
Background  Breast cancer is the most common cancer affecting women worldwide. Early detection through awareness and screening can help lower death rates significantly. However, in many areas, especially rural ones, awareness and knowledge about breast cancer are still low, leading to delayed diagnosis and treatment.Objectives  This study aimed to assess the knowledge of breast cancer and its screening methods among adult women attending the OPD of a tertiary care hospital and to identify factors influencing this knowledge.Materials and Methods  This hospital-based cross-sectional study was conducted among 400 adult women visiting the OPD of a tertiary care teaching hospital in Krishnagiri, Tamil Nadu. Data were collected on socio-demographic details, awareness of breast cancer symptoms, risk factors, and screening methods using a semi-structured questionnaire administered by an interviewer. Descriptive statistics and chi-square tests were used for analysis to find associations between different variables.Results  The average age of the participants was 42.3 years. Around 68.3% of women had heard of breast cancer, but only 55.7% were aware of screening methods. Better awareness was significantly linked to having a family history of breast cancer and higher education levels. Despite this, only 17.8% of women had undergone any screening, and 96.7% had poor overall knowledge of breast cancer based on composite scoring.Conclusion  The study reveals a large gap between awareness and knowledge regarding breast cancer and its screening methods. There is a need for focused efforts, especially for women with lower education and those from rural areas, to improve early detection and outcomes.
Keywords: Breast cancer; Awareness; Knowledge; Screening; Self-breast examination.; Risk factors